INTRODUCTION OF INTERACTIVE LEARNING IN PRIMARY SCHOOL PRACTICE (Pedagogy of Higher and Secondary Education, 2010)
The ways of introduction of the interactive teaching are exposed in the article, essence of the interactive teaching is lighted up; the groups of interactive methods of teaching are described.